Metal additive manufacturing MSc—a pioneering global master’s course for leaders of future manufacturing - Martina, Filomeno; Sun, Yongle; Krishnaswamy, Surya; Ganguly, Supriyo (Springer, 2026)
This chapter covers the design of world’s first MSc in Metal Additive Manufacturing (AM) with industry- and academia-driven considerations and objectives, as addressed in the European-Commission-funded project that saw the course developed over a period of three years. Then, the chapter covers the delivery and evolution of the course at Cranfield University, with its unique strengths and far-reaching activities in the field of large-scale metal AM. Finally, the chapter also covers case studies and innovative pedagogical tools introduced since 2019, providing a useful reference to broader stakeholders.
Keywords: 4014 Manufacturing Engineering; 40 Engineering; Additive manufacturing; Postgraduate education; MSc course; Certified training; Skilled workforce; Wire plus arc; Masters by research